Plasma Peptidylarginine Deiminase IV Promotes VWF-Platelet String Formation and Accelerates Thrombosis After Vessel Injury. Issue 5 (16th August 2019) - Sorvillo, Nicoletta; Mizurini, Daniella M.; Coxon, Carmen; Martinod, Kimberly; Tilvawala, Ronak; Cherpokova, Deya; Salinger, Ari J.; Seward, Robert J.; Staudinger, Caleb; Weerapana, Eranthie; Shapiro, Nathan I.; Costello, Catherine E.; et al.
Abstract : Rationale: : PAD4 (peptidylarginine deiminase type IV), an enzyme essential for neutrophil extracellular trap formation (NETosis), is released together with neutrophil extracellular traps into the extracellular milieu. It citrullinates histones and holds the potential to citrullinate other protein targets. While NETosis is implicated in thrombosis, the impact of the released PAD4 is unknown. Objective: : This study tests the hypothesis that extracellular PAD4, released during inflammatory responses, citrullinates plasma proteins, thus affecting thrombus formation. Methods and Results: : Here, we show that injection of r-huPAD4 in vivo induces the formation of VWF (von Willebrand factor)-platelet strings in mesenteric venules and that this is dependent on PAD4 enzymatic activity. VWF-platelet strings are naturally cleaved by ADAMTS13 (a disintegrin and metalloproteinase with thrombospondin type-1 motif-13). We detected a reduction of endogenous ADAMTS13 activity in the plasma of wild-type mice injected with r-huPAD4. Using mass spectrometry and in vitro studies, we found that r-huPAD4 citrullinates ADAMTS13 on specific arginine residues and that this modification dramatically inhibits ADAMTS13 enzymatic activity. Elevated citrullination of ADAMTS13 was observed in plasma samples of patients with sepsis or noninfected patients who were elderly (eg, age >65 years) and had underlying comorbidities (eg, diabetes mellitus and hypertension) as compared with healthy donors. This shows that ADAMTS13 is citrullinated in vivo. VWF-platelet strings that form on venules of Adamts13 −/− mice were immediately cleared after injection of r-huADAMTS13, while they persisted in vessels of mice injected with citrullinated r-huADAMTS13. Next, we assessed the effect of extracellular PAD4 on platelet-plug formation after ferric chloride-induced injury of mesenteric venules. Administration of r-huPAD4 decreased time to vessel occlusion and significantly reduced thrombus embolization. Conclusions: : Our data indicate that PAD4 in circulation reduces VWF-platelet string clearance and accelerates the formation of a stable platelet plug after vessel injury. We propose that this effect is, at least in part, due to ADAMTS13 inhibition. Abstract : Supplemental Digital Content is available in the text.